P058 Neural aperiodic activity as a novel objective measure of daytime somnolence. (7th October 2021) - Kang, T; Sarkar, P; Cross, Z; Chatburn, A; Singh, P; Johnston, S; Lushington, K; Yeo, A
Abstract: Background: Current assessment of excessive daytime somnolence (EDS) requires subjective measurements like the Epworth Sleepiness Scale (ESS), and/or resource heavy sleep laboratory investigations. Electroencephalographic (EEG) measures index intrinsic properties of the central nervous system. One such component is aperiodic neural activity which is thought to reflect excitation/inhibition ratios of neural populations and is altered in various states of consciousness. From this perspective, resting-state aperiodic activity may be a potential biomarker for hypersomnolence. We aim to analyse retrospective EEG data from patients who underwent a Multiple Sleep Latency Test (MSLT) and determine if aperiodic activity is predictive of subjective and objective measures of EDS. Methods: Participants having undergone laboratory polysomnogram (PSG) and next day MSLT will be grouped into those with and without sleepiness (mean sleep latency (MSL) of < 8min and > 10min respectively). Forty patients in each group (n=80) will be assessed. The primary objective is to compare the aperiodic slope between these groups, and secondary objectives comparing aperiodic activity with ESS and time of day. Data will be analysed using linear mixed-effect models. Simple linear regressions will be performed between the aperiodic slope and MSL and ESS, with R2 values used to estimate of effect size. Progress: Formal ethics approval has been submitted and is pending. Intended Outcome and Impact: In this exploratory study we hypothesise that EDS is associated with a lower aperiodic exponent/flatter slope, and hope to provoke further investigation of this metric as a novel biomarker for sleepiness.